Personal Hygiene Pada ODGJ Dengan Defisit Perawatan Diri Di Kelurahan Pondok Belakang Kota Bengkulu - Lolika Sapitri; Fera Yulianti; Tiara Tiara; Putri Karli; Becca Intan Lestari; Sinta Nurya (Universitas Dehasen Bengkulu, 2024)
Self-care deficit is the inability or difficulty in carrying out important daily activities such as bathing, eating, dressing, and maintaining hygiene. The ability to care for oneself independently is important to maintain physical and mental integrity and improve quality of life. Therefore, strategies to prevent self-care deficits are essential to improve the quality of life of homeless people with mental disorders. Self-care is an important aspect of maintaining overall health and includes activities that individuals undertake to improve physical, emotional and psychological health. However, some people lack the ability to care for themselves well, which can have a negative impact on their mental health. Self-care deficit is the inability or inability to perform self-care activities necessary to maintain health and well-being.